THE IMPLEMENTATION OF SIYASAH SYAR’IYAH PRINCIPLES IN THE CONSTITUTIONAL COURT DECISION REGARDING TO THE SIMULTANEOUS ELECTION 2019 - Prasetyoningsih, Nanik; Wijayanti, Septi Nur; Syaroni, Anang; Lailam, Tanto (Jurnal Hukum Progresif, 2019)
This study aims to examine the Constitutional Court's Decision which carries out General Elections simultaneously from the Syiyasah Syar'iyah perspective, especially on the principle of justice. This research is a doctrinal research and uses two approaches namely the statutory approach and the concept approach. Based on Syiyasah Syar'iyah's perspective, the decision of the Constitutional Court is fair for political parties participating in elections for people who are willing to become candidates/vice presidents, and for people who want to test their electability. This decision also aims to reduce the number of non-voter groups. The Constitutional Court's decision also contains the principle of unity and alliance, because it aims to stop the practical political interests that lead to the collapse of unity.